The Low Prevalence of Rheumatoid Arthritis in Two Regions of Serbia Based on Evidence-Based Data - Roksanda STOJANOVIC,; Radmila JOVICEVIC,; Branka GLOGOVAC,; Natasa RADOSAVLJEVIC,; Mirjana Zlatkovic SVENDA1, (Archives of Rheumatology, 2012)
Objectives: This study aims to present the results of three consecutive regional studies concerning the prevalence of rheumatoid arthritis (RA) based on medical documentation in two regions of Serbia. Patients and methods: Two representative regions of Serbia were chosen for the survey. The first region selected was the Zlatibor region located in the mountainous part of Western Serbia with a predominantly rural population. This study included patients registered in 1997. Two studies were also carried in the region of Belgrade, the capital. One of these studies was conducted in 2001 in the northern part of the city in Dobanovci, an urban suburb. The other took place in 2007 in Mladenovac, a southern suburb of Belgrade with a combined rural and urban population. The medical documentation for all patients diagnosed with chronic polyarthritis was reviewed to verify the diagnosis of RA according to the American Rheumatology College (ARC) 1987 revised criteria. The prevalence of RA was estimated based on the entire population over the age of 18 for Zlatibor region and over the age of 20 in the two studies in the Belgrade area. Results: The prevalence of RA in region Zlatibor was 0.253% (95% CI=0.217-0.288). In Dobanovci, the prevalence was 0.224% (95% CI=0.214-0.234), and it was 0.220% (95% CI=0.18-0.27) in Mladenovac. The estimated total number of patients with RA in Serbia was 14,445 out of an estimated 5,778,102 adult inhabitants in Serbia in 2009. Conclusion: The previous prevalence of RA obtained in a population study of Belgrade in the 1990s along with the data from these three studies demonstrates low values. These results are consistent with the values obtained in surrounding countries in the Mediterranean region.